2022
DOI: 10.1186/s13287-022-03129-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune recognition of syngeneic, allogeneic and xenogeneic stromal cell transplants in healthy retinas

Abstract: Background Advanced therapies using adult mesenchymal stromal cells (MSCs) for neurodegenerative diseases are not effectively translated into the clinic. The cross talk between the transplanted cells and the host tissue is something that, despite its importance, is not being systematically investigated. Methods We have compared the response of the mouse healthy retina to the intravitreal transplantation of MSCs derived from the bone marrow in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Recruitment of microglial cells (IBA1+) was frequently observed near the injection site and around the grafted area ( Fig. S10A-C ) 75 . The innate immune response observed in eyes grafted with punches from the WTC Act cell line was generally more robust compared to those from the WTC UDC cell line, with significant infiltration of macrophages and IBA1+ activated microglia within the graft ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recruitment of microglial cells (IBA1+) was frequently observed near the injection site and around the grafted area ( Fig. S10A-C ) 75 . The innate immune response observed in eyes grafted with punches from the WTC Act cell line was generally more robust compared to those from the WTC UDC cell line, with significant infiltration of macrophages and IBA1+ activated microglia within the graft ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Some evidance showed that in compare to autograft BM-MSC, the allograft or xenograft transplantation could change the retinal functionality and anatomical structures in animal model. Beside the morphological changes, microglial activation and migration to surround donor cells in allotransplantation and xenotransplantations, which was followed by CD45 + cells recruitment, the expression level of anti-inflammatory proteins was significantly lower in autograft group [ 595 ]. In addition, some individual characteristic of donor such as weight [ 596 ], age [ 597 ] and the rate of health [ 598 ] might affect the transplantation efficiency.…”
Section: Current Approaches Of Photoreceptor Regenerationmentioning
confidence: 99%
“…Autologous therapy involves the utilization of an individual's SCs or their secretions, which presents fewer concerns regarding compatibility and immunogenicity. Allogenic therapy employs SCs from a healthy donor of the same species, which still necessitates precise evaluation to prevent immunogenic reactions [ [13] , [14] , [15] , [16] ]. In xenogeneic approaches, the donor and recipient SCs originate from different species.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the use of human SCs in animal models has garnered significant attention for assessing their performance within the animal body. However, such invasive techniques employing SCs, such as bone marrow aspiration, raise considerable concerns and challenges [ [15] , [16] , [17] ]. Another non-invasive method for utilizing bone marrow-derived SCs involves their liberation into the peripheral circulation during therapies, stimulated through pharmacological agents and physical activities.…”
Section: Introductionmentioning
confidence: 99%